Exposure to organophosphate and cognitive performance in chilean rural school children: an exploratory study - María T. Muñoz Q; Verónica P. Iglesias Á; Boris A. Lucero M (Universidad de Antioquia, 2011)
Objective: to evaluate the presence of organophosphate metabolites (OP) in the urine of rural schoolchildren and estimate its association with their cognitive performance. Methodology: a cross-sectional exploratory study in which a total of 25 children were assessed. Cognitive functioning was measured using the WISC-III intelligence test. Additionally, the concentration of OP metabolites in their urine was tested. Results: 56% of the children had concentration levels above the detection limit for dimethylphosphate (DMP) and dimethyltiophosphate (DMTP). Moreover, 92% of them had the metabolite diethylphosphate (DEP) values on this limit. Regarding the WISC-III, the intelligence quotient (IQ) values below the average (IQ ˃ 90) correspond to: Total IQ = 60% performance IQ = 64%, verbal IQ = 52%, perceptual organization IQ = 60%, processing speed IQ = 95%, and freedom from distractibility IQ = 64%. An inverse association was found between the processing speed factor and DMTP (rs = -0.44, p = 0.014). Conclusions: results indicate that the rural schoolchildren whose urine was measured with OP metabolite biomarkers had been exposed to OP pesticides. A relationship was observed between the presence of OP metabolites and the cognitive performance factor of the WISC-III test. We believe it is appropriate to evaluate the effects of the presence of OP metabolites on cognitive functioning in a larger sample, while considering other exposure variables.